2011
DOI: 10.1002/app.34167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular weight of polyethylene on its flammability

Abstract: Polyethylene has been widely applied in our society and is known to burn well. Many researchers have been studying to control the flammability of polyethylene when adding several catalysts. However, this study has confirmed the effect of the molecular weight on the flammability of polyethylene. This article displays combustion states of two different molecular weights of polyethylene. The low molecular weight of polyethylene did not ignite and the high molecular weight of polyethylene ignited and burned well. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Dripping is obviously more severe for low‐viscosity materials. As a surprising example, Nakashima et al have shown that highly flammable polyethylene does not burn in a UL‐94 vertical test when its molecular weight is 35 000 g mol −1 or lower, due to severe dripping. Viscosity influences many other phenomena involved in flame retardancy: accumulation and migration of fillers at the surface, formation of a protective layer, intumescence, bubbling, etc.…”
Section: Impact Of Ageing On Flame Retardancymentioning
confidence: 99%
“…Dripping is obviously more severe for low‐viscosity materials. As a surprising example, Nakashima et al have shown that highly flammable polyethylene does not burn in a UL‐94 vertical test when its molecular weight is 35 000 g mol −1 or lower, due to severe dripping. Viscosity influences many other phenomena involved in flame retardancy: accumulation and migration of fillers at the surface, formation of a protective layer, intumescence, bubbling, etc.…”
Section: Impact Of Ageing On Flame Retardancymentioning
confidence: 99%
“…Factors that cause the fuel production rate to differ depending on the molecular structures include a difference in the thermal decomposition process of polymers. Two major thermal decomposition processes have been well characterized: random scission and chain‐end scission 19–22,40 . For PE, because carbon–carbon bonds in the main chain decompose dominantly by random scission, a significant amount of main chain scission is required to generate a sufficient quantity of volatile products.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature at which a sample weight decreases to 50% is the lowest for PS and the highest for PE. In addition, the decomposition products of PP and PE are mainly aliphatic, but many decomposition products of PS contain aromatic rings 19 . Therefore, the formation of soot particles proceeds easily for PS, which results in a red flame spreading rapidly and pronounced oscillations 41 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations